NPT1220-312, a TLR2/TLR9 Small Molecule Antagonist, Inhibits Pro-Inflammatory Signaling, Cytokine Release, and NLRP3 Inflammasome Activation - Agata Habas; Srinivasa Reddy Natala; Jon K. Bowden-Verhoek; Emily M. Stocking; Diana L. Price; Wolfgang Wrasidlo; Douglas W. Bonhaus; Martin B. Gill (International Journal of Inflammation)
Toll-like receptors (TLRs) play a critical role in innate immune system responses to damage-associated molecular patterns (DAMPs) and pathogen-associated molecular patterns (PAMPs). A growing body of evidence suggests that excessive TLR-mediated innate immune system activation can lead to neuronal damage and precipitate or perpetuate neurodegenerative diseases. Among TLR subtypes, both TLR2 and TLR9 have been implicated in neurodegenerative disorders with increased expression of these receptors in the central nervous system being associated with pro-inflammatory signaling and increased burdens of pathologic aggregated proteins. In the current study, we characterized the actions of a combined TLR2/TLR9 antagonist, NPT1220-312, on pro-inflammatory signaling and cytokine release in monocyte/macrophage-derived heterologous cells, human microglia, and murine and human whole blood. NPT1220-312 potently blocked TLR2- and TLR9-mediated release of inflammatory cytokines in monocyte/macrophage cells and in human microglia. NPT1220-312 also blocked TLR2-mediated activation of the NLR family pyrin domain containing 3 (NLRP3) inflammasome including IL-1β, IL-18, and apoptosis-associated speck-like protein containing a CARD (ASC) release to the culture medium of human differentiated macrophages. The ability of NPT1220-312 to inhibit TLR2 mediated pro-inflammatory release of chemokines and cytokines in situ was demonstrated using murine and human whole blood. Together, these findings suggest that blockade of TLR2 and TLR9 may reduce inappropriate production of pro-inflammatory cytokines and chemokines from peripheral and central immune cells and thus potentially provide therapeutic benefit in neuroinflammatory/neurodegenerative disorders.